Export Trend of Wooden Furniture from Malaysia - Ngooi, Voon Nee (2001)
The furniture sector is a major industry in Malaysia in terms of value of the products made and number of people employed. It plays an important role in increasing export earnings and contributes to the development of Malaysia in economy. This study was carried out to determine the trend of wooden furniture exported from Malaysia to major world regions and countries from year 1990- 1999. The trend in export was analysed using shares structure analysis on trade data of export value published by Malaysian Timber Industry Board (MTIB). Market percentages by regions and countries were calculated. Then exponential smoothing forecasting model was used to analyze the export trend of wooden furniture in year 2000. Results of the study showed that USA, Japan and Singapore were the most important trade partners with Malaysia during the period of 1990 to 1999. The world countries were classified into eight major regions according to their world geographical location. America, East Asia and ASEAN regions appeared as top three major importing regions from year 1990 to 1997. But later from year 1998 to 1999, European Union become the third important trade partners with Malaysia. The total trade value of wooden furniture is forecasted to inerease by 18.37% to the export value of RM3,776.8 million in year 2000. Generally, Malaysia's export of wooden furniture to the world market had been increasing over the last 10 years. The trend analysis of export values show that West Asia has the highest increase followed by Oceania/Pacific and Africa. If analysed on individual Country basis, UK is forecasted to have the highest increment followed by Netherlands, Australia and Korea. Local manufacturers should make efforts to maintain and increase export to the existing market. Besides that, they should concentrate on the regions and countries which show high increment in the forecasting export. It is suggested that the producers and relevant marketing agencies need to regular trend forecast the future export value. Further studies can be done on the internal and external factors that may affect the buying behaviour of foreign importers.